Engineered hexagonal boron nitride utilizing environmental friendly co-deposition technique - Maleque, Md. Abdul; Bello , K.; Ahmad , Zuraida (2014)

(untitled)
The hexagonal boron nitride (hBN) is a potential solid lubricating material; however, it has few limitations such as less surface activation, poor wettability, inhomogeneous mixture with substrate materials etc. This can be overcome via co-deposition of highly activated materials. Therefore, the present invention was aimed to co-deposit Ni-P alloy on hexagonal boron nitride (hBN) powder via electroless plating technique. The electroless nickel deposition was conducted in hypophosphite-reduced acid bath containing NiSO4 as the source of nickel. The characterization of co-deposited hBN was performed by means of scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), field emission scanning electron microscopy (FESEM) and x-ray diffraction (XRD) analyzer. The morphologies of Ni-P co-deposited hBN suggested a good metallurgical bonding and uniform distribution of the powders with the existence of Ni3P phase. Elemental mapping also confirmed the deposition of Ni-P onto hBN substrate. Hence, it can be claimed that the co-deposition provides a highly active surface of hBN powder. Furthermore, this co-deposited hBN powder can be used as an efficient solid lubricant for tribological application where introducing liquid lubricant is very difficult. This co-deposited hBN is expected to show better wettability with the metallic matrix as well as excellent thermal stability. The novelty in this invention is that a noble electroless deposition technique was successfully applied toco-deposit Ni-P on hBN powder.